IPv6 campus transition: A Central Luzon State University case study - Naagas, Marlon A.; Macabale Jr, Nemesio A.; Palaoag, Thelma D. (Institute of Advanced Engineering and Science, 2020)
Internet connections still use IPv4 as the primary address protocol and it is now facing exhaustion. However, academic institutions specifically in the Philippines should devise steps to address the exhaustion of IPv4. In this paper, this is brought to light as we present the IPv4 to IPv6 campus transition techniques to address the issue. The experiment is carried out in Central Luzon State University and is assessed if the university is able to adopt the IPv6 transition in their campus network. Two IPv6 transition mechanisms were implemented and tested. As a general result, it has been found out, through testbeds, that the dual-stack transition mechanism is more suitable than 6 to 4 tunnel broker. The results have also shown that 6 to 4 tunnel broker was outperformed by dual-stack transition mechanism in all areas and presents better performance. Additionally, results also showed that IPv4 presents slight advantages in terms of network performance than IPv6 with a very small percentage in difference, and this does mean that migration to IPv6 is possible without performance detriments. Furthermore, the results also provide a proof of concept for the university especially in the Philippines to consider IPv6 for future migration within their campus network.